(untitled) (Research, Society and Development, 2022)
Psychological diseases, such as depression, anxiety, are triggered by several factors related to changes in mental health, interfering not only with the professional’s quality of life, but also directly linked to the care provided to the patient. The study aimed to identify factors that predispose the occurrence of anxiety disorder and depression in Nursing professionals. This is an integrative literature review, in which the guiding question followed the PICo strategy: “What factors predispose the occurrence of anxiety disorder and depression in nursing professionals?” The literature search took place in the Scientific Electronic Library Online, in Latin American and Caribbean Health Literature and in the Nursing Database. Therefore, scientific articles were included that answered the guiding question, which were in Portuguese, available in full and free of charge in the selected databases from 2018 to 2022. Data analysis was based on the Thematic Content Analysis methodology proposed by Minayo (2001). It is concluded that among the factors that predisposed nursing workers to mental suffering during the COVID-19 pandemic, research highlighted the high demand for care, exhausting shifts, insufficient PPE, interpersonal conflicts in teams, the risk continuous illness and contamination of family members, as well as social isolation, which weakened the support networks of these professionals. In addition, the literature pointed to a high prevalence of symptoms of anxiety and depression among nursing professionals.